Legacy Effects of Agricultural Practices Override Earthworm Control on C Dynamics in Kiwifruit Orchards - Lago, María del Carmen F.; Barreal, M. Esther; Gallego, Pedro P.; Briones, María J. I. (Frontiers in Environmental Science, 2020)
In Galicia (NW Spain), kiwifruit (Actinidia chinensis var. deliciosa) is intensively produced using conventional practices (CONV) that ensure high yields, despite the fact that the excessive use of agrochemical inputs leads to soil organic matter depletion, increased water pollution and biodiversity losses. Although more sustainable practices have been implemented in the area (i.e. integrated, INT and organic farming, ORG), it remains unclear how these practices will affect C dynamics mediated by soil biota. Therefore, in this study, we investigated the effects of agricultural management practices and earthworm additions (macrofauna) on soil C losses (CO2 emissions and dissolved organic carbon (DOC)) in relation to the amount of bioavailable soil carbon (salt extractable organic carbon (SEOC) and microbial carbon indicators (microbial biomass or Cmic and the Cmic/Corg ratio)). The experimental design consisted of a 105-days laboratory incubation of intact soil cores collected in the field (40 from each agroecosystem) and earthworm additions over ambient (2.43 ± 0.05 g/earthworm) to half of the experimental units (+EW), with the remaining half acting as controls. Our results showed that earthworm additions led to significant increases in their abundance in all three management treatments, but with the ORG soils sustaining the greatest population sizes. However, no significant effect on soil C transformations were observed in response to these earthworm increases, and instead, legacy agricultural practices overrode macrofauna control on C turnover. Consequently, more C was lost from the CONV treatments than from the ORG ones (on average, 60% more CO2 and 53% more DOC) as a result of CONV practices promoting microbial-mediated processes and hence, amplifying C mineralization versus C stabilization. Furthermore, C release from the INT soils was intermediate between the other two treatments, which suggests that more sustainable farming practices could help in achieving climate change mitigation. These findings provide clear evidence of how local adaptation (at farm level) towards a more environmentally friendly land management could represent a promising strategy to increase soil C sequestration. Future agricultural approaches would need to incorporate the potential benefits from other agroecosystem services beyond those derived from productivity and market values.